Signifikansi Metodologi dalam Pengembangan Sosial Ekonomi Islam - Syahputra, Angga; Nurhayati, Nurhayati (Saree: Research in Gender Studies, 2022)
In the midst of a crisis that often occurs, Economic Methodology has become an object of study that is highly sought after or in demand by scientists. Every time the world experiences an economic crisis, it will encourage scientists to review matters relating to economic disciplines, be it in theory, science, or methodological science itself. As a new science, leading scientists began their activities to examine the appropriate methodology to produce Islamic economic theories where it was in accordance with the concept of Islamic epistemology, as well as to strengthen this methodological science to develop Islamic economics as a knowledge as well as to ensure scientific dynamics in the field of science. Islamic economics is going well and smoothly. For this reason, it is important to do this research through studies of the existing literature. This study resulted that the Islamic economic methodology was created based on an Islamic worldview where economic reality in a comprehensive perspective consists of spiritual, material, and moral dimensions. The discourse on Islamic economics methodology must be developed from only providing an Islamic perspective on the theories and structures of conventional economics (in other words, the Islamization of science), to something purer and giving birth to theories and developing Islamic scientific and economic structures themselves. AbstrakDi tengah krisis yang sering terjadi, Metodologi Ekonomi menjadi objek kajian yang sangat dicari atau diminati oleh para ilmuwan. Setiap kali dunia mengalami krisis ekonomi, maka akan mendorong para ilmuwan untuk mengkaji kembali hal-hal yang berkaitan dengan disiplin ilmu ekonomi, baik itu secara teori, ilmu pengetahuan, maupun metodologi ilmu itu sendiri. Sebagai ilmu yang masih baru, para ilmuwan terkemuka memulai aktivitasnya untuk mengkaji metodologi yang tepat untuk menghasilkan teori-teori ekonomi Islam di mana hal tersebut sesuai dengan konsep epistemologi Islam, serta memperkuat metodologi ilmu ini untuk mengembangkan ekonomi Islam sebagai sebuah ilmu pengetahuan sekaligus untuk menjamin dinamika keilmuan dalam bidang ilmu tersebut. Ekonomi Islam berjalan dengan baik dan lancar. Untuk itu, penelitian ini penting untuk dilakukan melalui kajian-kajian terhadap literatur yang ada. Penelitian ini menghasilkan bahwa metodologi ekonomi Islam diciptakan berdasarkan pandangan dunia Islam dimana realitas ekonomi dalam perspektif yang komprehensif terdiri dari dimensi spiritual, material, dan moral. Wacana metodologi ekonomi Islam harus dikembangkan dari hanya memberikan perspektif Islam terhadap teori dan struktur ekonomi konvensional (dengan kata lain, Islamisasi ilmu pengetahuan), menjadi sesuatu yang lebih murni dan melahirkan teori-teori serta mengembangkan struktur keilmuan dan ekonomi Islam itu sendiri.